Nursery Crop Selection and Market Niches - Gary W. Knox; Matthew Chappell (EDIS)
The ultimate success of an ornamental production operation hinges on the ability of that operation to successfully understand which genera, species, and/or cultivars to grow on a year-to-year basis. This 5-page fact sheet describes several important factors that must be considered in order to properly assess which ornamental crops should be grown and which market niches exist that may dictate crop selection. Written by Gary Knox and Matthew Chappell and published by the UF Department of Environmental Horticulture, November 2011. UF/IFAS Photo by Josh Wickham.